A Factor Analysis of Resilient Leadership of Institutional Personnel under Bangkok Office of Learning Encouragement - Rodprasert, Komchan; Tuntinakhongul, Ampapan; Sisan, Boonchan (Thammasat Journal, 2026)
The purpose of this research was to analyze the components of resilient leadership of institutional personnel under Bangkok Office of Learning Encouragement. The sample group consisted of 307 people from institutional personnel under Bangkok Office of Learning Encouragement, including educational administrators, school administrators, government teachers, sub-district non-formal education teachers, and non-formal education volunteer teachers. The sample was selected using stratified random sampling. The research instrument was a 5 point rating scale questionnaire with an Index of Item-Objective Congruence between 0.60 and 1.00, discrimination power between 0.314 and 0.866, and reliability of 0.964. The data were analyzed using exploratory factor analysis with principal component analysis and Oblique Rotation using Promax Rotation method. The results revealed that the components of resilient leadership of institutional personnel under Bangkok Office of Learning Encouragement consisted of 5 components with 28 variables, as follows: (1) Risk embracer: 8 variables, (2) Problem solver for sustainability: 6 variables, (3) Emotional Quotient leader: 6 variables, (4) Strong supporter and team player: 5 variables, and (5) Flexible and Lifelong Learner: 3 variables. These 5 components explained the resilient leadership of institutional personnel under Bangkok Office of Learning Encouragement with a cumulative variance of 53 percent.